Historical Significance of Labor's Increased Precariousness in Germany, the United Kingdom, and Spain. (23rd January 2019) - Arrizabalo, Xabier; Pinto, Patricia; Vicent, Lucía
Abstract: This article addresses the historical significance of the increasing precariousness of labor, even in the most advanced economies. Given the sterility of the mainstream approach, based on methodological individualism, we start from a Marxist critique of political economy, focusing on the laws that govern the process of capitalist accumulation and its contradictions. Within the framework of these laws, we analyze the tendency of labor exploitation to increase in a capitalist economy, linked to the exigencies of profitability due to the increasing difficulties of the valorization of capital. The precariousness of labor is studied around some of the main forms it adopts in three European economies: mini‐jobs in Germany, "zero‐hours contracts" in the United Kingdom, and false self‐employment, together with internship and training contracts, in Spain. Based on theoretical and empirical analysis, several conclusions are proposed to understand the extension and deepening of labor precariousness, built on the notions of overexploitation and destruction of productive forces, linked to current demands of capitalist accumulation.